Aktivitas Antioksidan pada Ekstrak Limbah Kulit, Biji, dan Ampas Jeruk Siam Kintamani (Citrus nobilis et reticulata) dengan Pelarut Metanol - Ni Kadek Novia Puspita Dewi; Pande Ayu Naya Kasih Permatananda; Desak Putu Citra Udiyani; Putu Nita Cahyawati; Ni Wayan Erly Sintya Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the antioxidant activity of waste extracts from the peel, seeds, and pulp of Kintamani tangerines and to implement a practical approach to by-product management based on a zero-waste system. The method used is a pure experimental study with a post-test only design. Extraction was carried out through repeated maceration using methanol as a solvent. Antioxidant activity was tested using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method and analyzed with a UV-Vis spectrophotometer at a wavelength of 517 nm. The results showed that the peel extract of Kintamani tangerines could fade the purple color of the DPPH solution, whereas the seed and pulp extracts did not show a significant change. The IC50 values were 136.17 ppm for the peel extract, 6727.86 ppm for the seed extract, and 497.57 ppm for the pulp extract. In conclusion, the peel extract of Kintamani tangerines exhibited the highest antioxidant activity among the three extracts, categorized as moderate based on Blois' classification. Keywords: Antioxidant Activity, Pulp, Kintamani Tangerine, Seed, DPPH, Peel